Bilateral Investment Treaty and Foreign Direct Investment: Game Analysis Based on the Signal Model - Svitlana LUKASH; Sen HU; Nataliia MASLAK (Communications of International Proceedings, 2020)
The bilateral investment treaties (Bilateral Investment Treaty, BIT) are a signal delivered to investors by the host country. The effective condition of the signal lies in the difference of BIT compliance cost, so investors have the basis to distinguish different types of host countries. Based on Jan Peter Sasse analysis, the signal effect mechanism of the bilateral investment treaty is analyzed by using the signal model under incomplete information. The game between host country and investor is the signal transmission game of incomplete information. For both types of host countries, it is advantageous to sign a BIT. The host country adopts the strategy of "signing BIT" and makes a credible commitment of property right protection to investors through BIT. BIT gives the host country a competitive reputation advantage in attracting capital. Under the constraints of the investment agreement, investors can anticipate the behavior of the host country, and foreign investors are more inclined to invest in the signed or effective BIT countries. For investors, on the premise that the expected return of investors is positive, if the host country signs BIT, it will form a positive investment incentive for investors. When the expected return of the investor is zero, the investor can be considered as a potential investor (the investor may or may not invest). In this case, whether the host country "signs BIT" is more sensitive to the influence of the investor in judging the type of the host country.
Keywords: bilateral investment treaty; foreign direct investment; incomplete information; pooling equilibrium; separating equilibrium.